Strategies for Creating Quality Managers Through Talent Management, Job Enrichment and Assessment - Fauzi Jaya Sakti, Reza; Fachrial, Peppy; Panjaitan, Maludin; Hartini, Hartini; Normi, Siti (Green Publisher, 2024)
Literature review research on strategies to create quality managers through talent management, job enrichment, and assessment is a scientific literature article in the scope of human resource management science. The purpose of writing this literature article is to create a hypothesis related to the influence between variables which can later be used for further research in the scope of human resource management. The research approach used is descriptive qualitative. The data collection technique uses literature studies. The data used in this descriptive qualitative approach comes from previous research that is relevant to this research and is sourced from academic online media such as the Scopus Elsevier Journal, Emerald, Sage, WoS, Sinta Journal, DOAJ, EBSCO, Google Scholar, and digital reference books. The results of this literature review research are: 1) Talent Management plays a role in Creating Quality Managers; 2) Job Enrichment plays a role in Creating Quality Managers; and 3) Assessment plays a role in Creating Quality Managers.